2014
DOI: 10.1248/bpb.b14-00487
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic Effects of Mammalian Target of Rapamycin Inhibitors in a Mouse Model of Oxygen-Induced Retinopathy

Abstract: Ocular pathologic angiogenesis is a causative factor for retinopathy of prematurity, diabetic retinopathy, and age-related macular degeneration. In the present study, we examined the effects of rapamycin and everolimus, inhibitors of mammalian target of rapamycin (mTOR), on retinal pathologic angiogenesis in mice with oxygen-induced retinopathy (OIR), an animal model of proliferative ischemic retinopathy. Mice were exposed to 80% oxygen from postnatal day (P) 7 to P10, and were then brought into room air and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…Building upon previous research targeting the mTOR signaling pathway as a therapeutic for various diseases, a number of studies have investigated the role of mTOR in the pathological conditions of the retina 15, 16, 17, 19, 29, 30. Using mTOR pathway inhibitors, recently it has been shown that blocking mTOR signaling conferred protection against the formation and progression of CNV 16, 18, 19, 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon previous research targeting the mTOR signaling pathway as a therapeutic for various diseases, a number of studies have investigated the role of mTOR in the pathological conditions of the retina 15, 16, 17, 19, 29, 30. Using mTOR pathway inhibitors, recently it has been shown that blocking mTOR signaling conferred protection against the formation and progression of CNV 16, 18, 19, 30.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR was shown to be a critical factor in the angiogenesis processes of various retinal pathologic conditions, including AMD, retinopathy of prematurity, and diabetic retinopathy 15, 16, 17. Other recent studies demonstrated that autophagy induced by mTOR inhibition promoted the survival of retinal pigment epithelial (RPE) cells under toxic conditions,18, 19, 20 indicating that the development of new therapeutic modalities for managing AMD may crucially include mTOR signaling pathway regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The level of phospho-VEGFR2 did not significantly vary between αBrdU and 11C7 treatments (Supporting Information Figure S6b) in P13 OIR retina. The activation of signaling cascades involved in pathological angiogenesis such as P-Stat3 (Sun et al, 2015), P-S6 (Yagasaki et al, 2014), and P-Erk1/2 (Yu et al, 2016) were also not influenced by 11C7 injection (Supporting Information Figure 6a,b). These results suggest that 11C7 may promote in part vascular growth by decreasing S1PR2 in endothelial cells.…”
Section: C7 Alters the Expression Of Nogo-a And S1pr2 In Oxygen-imentioning
confidence: 98%
“…Therefore, in this study, newborn (P0) male and female mice (11∼14 mice) were placed in hyperoxic conditions (75% oxygen) in an oxygen-regulated chamber with their nursing mother. Oxygen concentrations were measured with a sensor placed inside the cage and regulated by an oxygen controller (ProOx110; Biospherix, Redfield, NY), as reported previously (Yagasaki et al, 2014a). After completing 48 or 96 hr of hyperoxia, mice were returned to normoxia (room air).…”
Section: Effect Of High-concentration Oxygen Exposure On the Retinal mentioning
confidence: 99%